Progesterone can enhance consolidation and/or performance in spatial, object and working memory tasks in Long–Evans rats - Frye, Cheryl A. (2009)
Progesterone has a ubiquitous role in reproduction and fitness and may influence cognitive performance. We examined the effects of administration of progesterone (a regimen that facilitates sexual behaviour) on consolidation of complex information in Long–Evans rats, Rattus norvegicus, that may be relevant for social engagement. We also examined the effects of subcutaneous progesterone administration (4 mg/kg versus oil vehicle placebo) on memory of ovariectomized rats during various cognitive tasks. Ovariectomized rats that received progesterone, versus the vehicle, immediately post-training were better able to find a hidden platform in the water maze. In a recognition task, rats that received progesterone spent more time in the novel arm of the Y-maze task than rats that received the vehicle. Ovariectomized rats that received progesterone immediately after training spent significantly more time exploring a novel object (compared to a familiar object) than did vehicle-administered rats. When socially relevant stimuli (i.e. objects with the scent of familiar or novel conspecifics) were used in the social cognition task, ovariectomized rats that received progesterone spent more time exploring the object with the novel conspecifics’ scent than did vehicle-administered rats. Pairing of progesterone, but not the vehicle, conditioned a place preference to the originally nonpreferred side of the conditioning chamber. We found no significant differences in motor activity measures in these tasks due to progesterone treatment. These results suggest that progesterone’s effects to improve cognitive processes with nonsocial and socially relevant stimuli, as well as have reinforcing effects, may underlie some of its salient effects on reproduction-related behaviours.